2014
DOI: 10.1007/s12602-014-9157-3
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus pentosus B231 Isolated from a Portuguese PDO Cheese: Production and Partial Characterization of Its Bacteriocin

Abstract: Bacteriocin B231 produced by Lactobacillus pentosus, isolated from an artisanal raw cow's milk protected designation of origin Portuguese cheese, is a small protein with an apparent relative mass of about 5 kDa and active against a large number of Listeria monocytogenes wild-type strains, Listeria ivanovii and Listeria innocua. Bacteriocin B231 production is highly dependent on the type of the culture media used for growth of Lact. pentosus B231. Replacement of glucose with maltose yielded the highest bacterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…It is also registered high levels of accumulated bioactivity of pentocin B231 when the microorganism reached the stationary phase (Guerreiro et al . ). It is suggested that maximum bacteriocin production toward the end of the exponential growth phase could be due to delayed formation of the necessary enzymes (Cheigh et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…It is also registered high levels of accumulated bioactivity of pentocin B231 when the microorganism reached the stationary phase (Guerreiro et al . ). It is suggested that maximum bacteriocin production toward the end of the exponential growth phase could be due to delayed formation of the necessary enzymes (Cheigh et al .…”
Section: Discussionmentioning
confidence: 97%
“…As mentioned before, L.pentosus B231 presented good growth in MRS supplemented with 4% NaCl (Guerreiro et al . ). However, it has also been recognized that LAB growth can be inhibited by osmolarity (Neysens et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, recent studies have sought to investigate the probiotic potential of LAB isolated mainly from fermented products. Microorganisms from extra-intestinal sources have shown interesting properties, such as bacteriocin production, adherence to epithelial cells and mucus, and resistance to gastric pH and bile (Zoumpopoulou et al, 2008;Klayraung and Okonogi, 2009;Barbosa et al, 2014;Guerreiro et al, 2014;Tulumoğlu et al, 2014). In clinical studies, several species of Lactobacillus were able to reduce diarrhea and respiratory infections, and ameliorated symptoms of atopic dermatitis (Ciszek-Lenda et al, 2011;Nermes et al, 2011).…”
Section: Discussionmentioning
confidence: 99%